Relationship between body image and somatotype profile in young women - Marcela Rodrigues Castro; Fabiane Frota Rocha Morgado; Ana Clara Souza Paiva; Fernanda Lopes Magre; Diego Giulliano Destro Christofaro; Ismael Forte Freitas Junior (Desafio Singular, 2017)
This study aimed to investigate associations among body dissatisfaction, behaviors, feelings, and beliefs related to the body - and somatotypical profile. The sample included 142 undergraduate female students (21.81 ± 3 years) who underwent to assessment of Body Mass Index and somatotype, according to the World Health Organization and Heath-Carter protocols, respectively. To assess body image the following instruments were applied: Body Shape Questionnaire, Body Attitudes Questionnaire, Body Image Avoidance Questionnaire, Sociocultural Attitudes Towards Appearance Scale, Self-Subject Silhouettes To the analysis data we proceeded to multivariate analysis of variance (MANOVA one-way). As the main result, we find that body dissatisfaction, body avoidance and negative attitudes about appearance components are linked to each other and they are influenced by body profiles with mesomorphic and endomorphic predominance. We conclude that the somatotype profile can be an important predictor of changes in body image and is indicated for tracking risk groups.